ANALISIS KORESPONDENSI PADA POLA HUBUNGAN ANTARA JENIS BENCANA DAN STATUS KORBAN DI SUMATERA TAHUN 2024 - Muhammad Al-Farisy; Riska Mulyani; M. Riswan; Tarisa Humaira; Lathifah Putri Adani (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
CORRESPONDENCE ANALYSIS OF THE RELATIONSHIP PATTERN BETWEEN DISASTER TYPES AND VICTIM STATUS IN SUMATERA IN 2024 This study analyzes the relationship between provinces, types of disasters, and types of disaster victims in 10 provinces on Sumatra Island using correspondence analysis. The data includes seven disaster types and five victim categories from Aceh, North Sumatra, West Sumatra, Riau, Riau Islands, Jambi, Bengkulu, South Sumatra, Bangka Belitung Islands, and Lampung. Descriptive results show floods as the most frequent disaster, while the "suffering victims" category appears most often. The chi-square test yields a p-value < 2.2e-16, indicating significant relationships between all variable combinations. The correspondence plot reveals distinct patterns: Lampung often faces extreme weather and earthquakes; West Sumatra and Riau are prone to landslides; Riau Islands and Aceh to forest and land fires; and Bengkulu to drought. Victim distribution also varies, West Sumatra reports more displaced victims, while most other provinces have predominantly suffered victims. In terms of disaster impacts, landslides are linked to fatalities, forest and land fires to displacement, and floods to suffering and missing victims. These findings highlight the interconnectedness of regions, disaster types, and victim impacts, offering important insights for disaster risk management and mitigation efforts across Sumatra.